Exploring Cancer Patient Navigation Programs Across the Globe: A Scoping Review - Nuzulullail, Agung Subakti; Agustin, Agustin; Dudini, Amalia Khasanah Ima; Fakhriyah, Anya Bunga; Annurahman, Arif; Sarifudin, Asri Wati; Hartini, Sri (Indonesian Journal of Cancer, 2025)
Background: The lack of quality cancer care is still experienced by cancer patients around the world. Cancer patient navigation was introduced to address this problem by eliminating the barriers encountered by patients. However, currently, the implementation of this program in each country varies according to the country's conditions. This study aims to explore the implementation of cancer patient navigation in several countries.Methods: A Scoping review used scientific articles from four databases, including SpringerLink, ProQuest, EBSCOhost, and Wiley. The selected articles were original research articles with publication years from 2020 to 2024. Determination of research questions and keywords used the P (Problem): practice and existence of cancer patient navigators; C (Concept): cancer patient navigators; and C (Context): various countries in the world. A total of 12 selected articles were related to the implementation of cancer patient navigation in 12 different countries. The research question was "How is the Implementation of Cancer Patient Navigators in Various Countries?"Results: A total of 12 articles were identified and providing an overview of three main themes related to cancer patient navigation. The themes were factors that influence services, the role of cancer patient navigators, and the benefits of cancer patient navigation. Implementation of cancer patient navigator (CPN) in various countries has demonstrated its effectiveness in overcoming cultural, logistical, financial, and healthcare access barriers through a personalized, multidisciplinary, and community-based approach to improve the quality of cancer diagnosis, treatment, and continuity of care.Conclusions: All studies explained that the services provided by CPN programs tended to be similar, although the locations and facilities differed in each country. Future researchers are advised to explore CPN implementation models in improving access, adherence, and clinical outcomes of cancer patients.